القاضي عياض ومواقفه السياسية 476هـ - 544هـ 1083 - 1149 م - مصباحي، إبراهيم, كاكي، وليد (جامعة الوادي university of Eloued, 2019)
الملخص: هذه الدراسة ن تسلط الضوء على موضوع القاضي عياض وعلاقته بالسياسة،حيث تناولنا في بحثنا هذا الذي يتكون من فصلين،الفصل الأول يختص بالسيرة الذاتية والعلمية للقاضي عياض، فيندرج. تحت السيرة الذاتية نسب القاضي عياض وأصله وهو عربي ينتهي إلى يحصب بن مدرك، وأيضا مولده وقد ولد في سبتة سنة 476ه/1083م ، ونشأته وأخلاقه، ووفاته وأسبابها، ثم تناولنا في السيرة العلمية طلبه للعلم في سبتة ورحلاته في طلب العلم إلى قرطبة ومرسية والمرية وغيرها وشيوخه، حيث يزيد شيوخه عن مائة شيخ ،وتلاميذه ومؤلفاته، ثم سلطنا الضوء على حياته السياسية في الفصل الثاني فذكرنا وظائفه السياسية من تولي القضاء في سبتة وغرناطة وداي، ثم تناولنا علاقته السياسية بالدول التي عاصرها كدولة المرابطين ودولة الموحدين، فكانت علاقته بدولة المرابطين إيجابية عنوانها السمع والطاعة والموالاة، لكن رغم ذالك لايرضى بظلم والتعسف ويحارب ذالك كما شهدناه أيام قضائه بغرناطة، وأما علاقته بالموحدين فشابها التوتر والنزاع بسبب أنه لا يرى بإمامتها ولم يبايعهم إلا على الإكراه، حتى انتهى به الأمر مغربا عن وطنه ليتوفى سنة 544ه/1149م. Abstract This study sheds light on the subject of Judge Ayyad and its relation to politics. In this research we discussed two chapters. The first chapter deals with the curriculum vitae of Judge Ayyad. Under the curriculum vitae, Judge Ayyad and his origin, an Arab who ends up reaping Ben Medrak and also his birth, was born in Ceuta in 476 AH / 1083 AD, and his origin and morals, and his death and causes. Then we dealt with his scientific request for knowledge in Ceuta and his trips to seek knowledge of Cordoba, Marsa, And elders, where more than a hundred elders, and his disciples and his writings,Then we shed light on his political life in the second chapter. We mentioned his political functions from taking over the judiciary in Ceuta, Granada and Dai. Then we dealt with his political relationship with the countries that he experienced as Almoravid and Almohad states. His relationship with the Almoravid state was positive, hearing, obedience and loyalty. This is what we witnessed during the days of his stay in Granada. His relation with the Almohads was similar to the tension and conflict because he did not see the imams and did not sell them except on duress, until he ended up exiting his homeland to die in 544 AH / 1149.
مذكرة ماستر تاريخ تخصص تاريخ الغرب الإسلامي في العصر الوسيط
Keywords: القاضي عياضي; Juge Ayad; Judge Ayad